Violence and mental suffering among men in primary health care - Albuquerque, Fernando Pessoa de; Barros, Claudia Renata dos Santos; Schraiber, Lilia Blima (Revista de Saúde Pública, 2013)
OBJECTIVE: To analyze the association between male mental health problems and violence experienced. METHODS: Cross sectional study with 477 males aged between 18 and 60, users of two primary healthcare centers in Sao Paulo, SP, Southeastern Brazil. The selection for the sample was based on a sequentiality criterion, according to the order of arrival of the users. Sociodemographic and health characteristics and reports of having experienced violence at any time and/or having witnessed violence in childhood were collected. Information was also collected on the use of mental health services and/or psychological complaints/diagnoses during consultation at medical clinics by reading medical records, to categorize the dependent variable "mental suffering". The variables were described as absolute and relative frequencies. The association was tested using a confirmatory Poisson model with robust variance adjusted for age, marital status, education, violence witnessed in childhood and psychoactive substance use. RESULTS: The prevalence of mental suffering was 29.4%. Mental suffering was associated with experiencing repeated physical and/or sexual violence (RP 1.75, 95%CI 1.13;2.72). The association with a single episode of violence lost significance after the inclusion of psychoactive substance use in the model. Analysis of the fraction attributable to repetitive physical and/or sexual violence for the mental suffering of the men, verified it as 30.4%. CONCLUSIONS: The relationship between violence and mental suffering, already highlighted in studies with women, is also relevant to men's health, drawing attention to the similar need of identification, in the health services, of situations of violence experienced by the male population. For men, this relationship was shown to be influenced by the presence of psychoactive substance use; a situation which must be dealt with, more and in a better way, by the health care service.